2018
DOI: 10.1007/s10198-018-0997-8
|View full text |Cite
|
Sign up to set email alerts
|

Health polarization and inequalities across Europe: an empirical approach

Abstract: This paper examines inequality and polarization in self-assessed health, contributing towards the limited research existing on health economics. We use data from the European Health Interview Survey (EHIS) to investigate the relationship between health inequality and polarization across 27 European countries in two periods: 2006-2009 and 2013-2015. As our key variable is of an ordinal nature, we employ median based measures. Our empirical results suggest that Greece is the country with the highest level of hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Notwithstanding, we have identified new insights on the interdependence of health within households. Further research is still needed to identify new interventions and policies that impact on mental health and inequalities across Europe [28].…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, we have identified new insights on the interdependence of health within households. Further research is still needed to identify new interventions and policies that impact on mental health and inequalities across Europe [28].…”
Section: Discussionmentioning
confidence: 99%
“…The economic crisis has taken a severe impact on Greek society in terms of unprecedented high unemployment rates, increased poverty, and exacerbated economic inequality. Pascual et al [4] investigated the magnitude of health inequalities and health polarization across the 27 European Union countries using the European Health Interview Survey (EHIS) over two periods: 2006-2009 and 2013-2015. Their findings revealed that Greece is the country with the highest levels of health polarization in both periods.…”
Section: European Health Model In Disputementioning
confidence: 99%
“…A N U S C R I P T used epidemiological surveys [3][4][5][6][7]. Therefore, it should not disregard health data obtained through the individuals' SAH as it provides valuable information about their well-being.…”
Section: A C C E P T E D Mmentioning
confidence: 99%